The lipid peroxidation system and connective tissue metabolism in patients with lumbar spinal stenosis - Leontyeva, Frieda; Fedotova, Inga; Ivanova, Iryna; Korzh, Iryna (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2012)
The purpose of the present work was to assess the state of the system of lipid peroxidation and connective tissue metabolism in patients with lumbar spinal stenosis (LSS). The study was performed on 317 patients with presence and absence of a neurological deficit against a background of LSS. More severe biochemical changes in the oxidation system were detected in patients with neurological disorders. An analysis of correlations between the accumulation of lipid peroxidation products in blood serum and the biochemical changes, which characterize the state of connective tissues, revealed that the extent of accumulation of diene conjugates and thiobarbituric acid products as markers of the state of the lipid peroxidation system in patients produced its effect on inflammatory and, as a result, destructive processes in the connective tissue in case of LSS and might contribute to the mechanism of manifestation of the clinical signs of the above disease.